The cobra clash - Patton, Jack (Battle bugs, 2015)
"Max Darwin is summoned back to Bug Island to discover the island in turmoil. Spike has vanished, and his disappearance has all the hallmarks of one of General Komodo's dastardly schemes. Max soon discovers that Spike has been bugnapped and is being held prisoner in the Reptilian Empire! Max must devise a daring rescue plan that involves traveling deep into enemy territory."--Publisher.